Hedgehog inhibition reduces angiogenesis by downregulation of tumoral VEGF‐A expression in hepatocellular carcinoma. Issue 4 (1st August 2013) - Pinter, Matthias; Sieghart, Wolfgang; Schmid, Monika; Dauser, Bernhard; Prager, Gerald; Dienes, Hans Peter; Trauner, Michael; Peck‐Radosavljevic, Markus
Abstract : Background: Dysregulation and activation of Hedgehog (Hh) signalling may contribute to tumorigenesis, angiogenesis, and metastatic seeding in several solid tumours. Objective: We investigated the impact of Hh inhibition on tumour growth and angiogenesis using in‐vitro and in‐vivo models of hepatocellular carcinoma (HCC). Methods: The effect of the Hh pathway inhibitor GDC‐0449 on tumour growth was investigated using an orthotopic rat model. Effects on angiogenesis were determined by immunohistochemical staining of von Willebrand factor antigen and by assessing the mRNA expression of several angiogenic factors. In vitro, HCC cell lines were treated with GDC‐0449 and evaluated for viability and expression of vascular endothelial growth factor (VEGF). Endothelial cells were evaluated for viability, migration, and tube formation. Results: In the orthotopic HCC model, GDC‐0449 significantly decreased tumoral VEGF expression which was accompanied by a significant reduction of microvessel density and tumour growth. In HCC cells, GDC‐0449 had no effect on cell growth but significantly reduced target gene regulation and VEGF expression while having no direct effect on endothelial cell viability, migration, and tube formation. Conclusions: Hh inhibition with GDC‐0449 downregulates tumoral VEGF production in vitro and reduces tumoral VEGF expression, angiogenesis, and tumour growth in an orthotopic HCC model.